Adverse reactions to drugs and their physico-chemical properties. Issue 673 (November 1981) - Lewis, J. G.
Abstract : Physico-chemical factors can be related to adverse reactions. Their importance is that safer drugs can be made at the stages of design, delivery and metabolism.